URGENSITAS PENGUATAN KOMPETENSI PENYELESAIAN SENGKETA EKONOMI SYARIAH DI PENGADILAN AGAMA DALAM MENGAWAL PERTUMBUHAN INDUSTRI KEUANGAN SYARIAH DI INDONESIA - Suhartono, Suhartono (Justicia Islamica, 2017)
The appreciation of the reputation and achievements of the Religious Courts continued to flow from experts and credible international survey organizations. Among others, Mark Cammack[1], Daniel S. Lev[2], Markus Zimmer, Cate Summer[3], Tim Lindsey, CJ Diana Bryant, Yoshiharu Matsuura etc. Meanwhile, the survey agency, among others, The Asia Foundation[4], ACNielsen, UN Women -institute under the auspices of the United Nations-, IALDF, etc. that in essence they satisfy with the performance of the Religious Court. This condition is contradictory to the situation in their own country, even though de jure has received an additional mandate (competence) as mandated by Article 49 of Law No. 3 of 2006, but de facto skepticism and pessimism in some quarters, indirectly weaken and reduce the competence of the Religious Court. This is often done by a handful of party, unsupported by valid research data. In fact, the true increase Religious Courts competence born from the womb of reform, but already at the age of eight years of this, it still has not gained the trust and support of the maximum. Expectations of economic actors to the sharia court Religion should be coupled with efforts to strengthen the real from stakeholders to the Religious Court can maximize its role in escorting the growth of the Islamic finance industry, that will be the focus of study in this paper.[1] Guru besar Southwestern Law School, Los Angeles California USA, dalam bukunya: Islamic Law in Contemporary Indonesia; Ideas and Institutionsâ (2007), ia mengatakan, Peradilan Agama merupakan kisah sukses dalam sistem hukum yang disfungsional (disfunctional legal system) di Indonesia.[2] Dia mengakui bahwa Peradilan Agama merupakan pengecualian dari persepsi publik yang kurang baik terhadap pengadilan, menurut Lev, Pengadilan Agama telah bekerja dengan baik.[3] Cate Summer dan Tim Lindsey dalam bukunya, Courting Reform: Indonesiaâs Islamic Courts and Justice for the Poor, mengatakan:â.. as champion within the judicial system of justice and access to justice reform in Indonesia......â. âFrom this perspective, the Relegious Court can be seen as one of the most successful of Indonesiaâs judicial institutions. This is in some senses, ironic, as these courts have also historically been neglected by the state...â.[4] Lihat Anonim. 2005. Citizensâ Perceptions of the Indonesian Justice Sector (Survey Report). Jakarta: The Asia Foundation. hal. 63 hasil surveynya menyatakan Peradilan Agama sebagai satu-satunya institusi penegak hukum yang memiliki performance paling baik, dibandingkan lembaga penegak hukum lainnya.